Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Sulfonamide- and hydrazine-based palladium catalysts: stable and efficient catalysts for C-C coupling reactions in aqueous medium - Kumar, N. S. C. Ramesh; Raj, I. Victor Paul; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2007)
Syntheses of a novel family of sulfonamide-based palladium complexes and phenylhydrazine-based palladacycles are described. These catalysts are thermally stable, and not sensitive to air and moisture and some are completely soluble in water. These catalysts have shown excellent activity (good yields and high turnover numbers) and product selectivity in several arylation reactions including Suzuki, Heck, and Sonogashira reactions carried out totally under aqueous conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: arylation reaction; Heck reaction; palladium catalyst; Sonogashira reaction; Suzuki coupling reaction

Asymmetric synthesis of (S)-vigabatrin (R) and (S)-dihydrokavain via cobalt catalyzed hydrolytic kinetic resolution of epoxides - Raj, I. Victor Paul; Sudalai, A. (Tetrahedron Letters, 2008)
A concise route to the asymmetric synthesis of (S)-vigabatrin(R) and (S)-dihydrokavain has been described using Co-catalyzed hydrolytic kinetic resolution of racemic epoxides and regiospecific opening of terminal epoxides with dimethylsulfonium methylide as the key steps. (C) 2008 Elsevier Ltd. All rights reserved.

H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins